Development of harmonized HPTLC methods for determination of polyphenolic compounds of tinctures - K. O. Khokhlova (The State Expert Center of the Ministry of Health of Ukraine, 2020)
The tincture is a traditional liquid dosage form for the pharmaceutical market of Ukraine. Today, the range of the tinctures of Ukrainian manufacturers has 21 different items, while only six monographs on different tinctures are included in the State Pharmacopoeia of Ukraine. For standardization of tinctures, different combinations of specific and non-specific physical and chemical methods are used. The high-performance thin-layer chromatography (HPTLC) is a modern and specific chromatographic method, that can be used for the identification of polyphenolic substances responsible for a wide range of pharmacological activities of the tinctures. The purpose of the study was to identify and compare chromatographic fingerprints (images of chromatograms and peak profiles from images) of flavonoids and phenylpropanoids of 10 tinctures of Ukrainian production in the harmonized mobile phases, to select for each tincture the specific marker zones, to determine the suitability of the specified chromatographic conditions for standardization of the tincture and the possibility to perform in these conditions the quality control for several different tinctures in-parallel. The objects of the investigation were Hawthorn tincture, Peppermint tincture, Sage tincture, Motherwort tincture, Calendula tincture, Sophora tincture, Echinacea purpurea tincture, Valerian tincture, Peony tincture, Eucalyptus tincture. The research was carried out using the HPTLC method in the HPTLC automatic herbal system (CAMAG, Switzerland) on the base of two laboratories. For each investigated tincture, the determination and comparison of HPTLC chromatographic fingerprints (images and peak profiles of images) of flavonoids and phenylpropanoids obtained in different harmonized mobile phases were performed. In the harmonized chromatographic conditions the difference in separation of the bioactive substances was determined; the characteristic marker substances of the tinctures were identified; the suitability of the mobile phase for individual analysis of the tincture or in-parallel analysis of different tinctures on the same plate were determined; the possibility to replace one mobile phase by another, if needed, was determined. Proposed HPTLC methods were developed using modern procedure and approach. These allow to reduce of the scope and time of analysis, optimize the economical and labor costs. The findings are of special importance for the pharmaceutical manufacturers and quality control laboratories that perform analysis on a large scale.